2014 Handbook of IMF Facilities for Low-Income Countries. (Policy Papers; Policy Paper ;, 2014)
This Handbook, an updated version of a similarly titled document issued in May 2012 (IMF, 2012c), provides guidance to staff on the financial facilities for low-income countries (LICs) that became effective in January 2010 (ECF, SCF, and RCF), and the PSI, including modifications to the guidance resulting from the Review of Facilities for Low-Income Countries (IMF, 2012e and 2013d) and the Review of Eligibility to Use the Fund's Facilities for Concessional Financing (IMF, 2013c). Designed as a comprehensive reference tool for program work on low-income countries, the Handbook also refers, in summary form, to a range of relevant policies that apply more generally to IMF members. As with all guidance notes, the relevant IMF Executive Board decisions, including the terms of the various LIC Trust Instruments that have been adopted by the Board, remain the sole legal authority on the matters covered in the Handbook.